The Caryatid from Osor (Apsorus) - Šmid, Katarina (Studia universitatis hereditati, 2025)
The study examines the marble female statue from Osor (Apsorus; now in the Museo Archeologico Nazionale di Venezia, inv. no. 162-A), traditionally referred to as Medea, Caryatid, or Muse-Caryatid. The figure is dressed in a chiton and diplex, it was carved with an unfinished back, suggesting placement against a wall. Stylistic and iconographic analysis of its posture and drapery associate it more closely with the Tralles/Cherchell type of caryatides than with the Erechtheion prototypes, thereby underscoring its primarily decorative rather than structural purpose. The statue’s archaizing hairstyle and drapery, together with other sculptural finds from Apsorus, suggest an Early Imperial date of production, most likely within the Augustan or Julio-Claudian period. The absence of a clear archaeological context precludes certainty about its original function, but its decorative role – possibly within a public building or elite residence – appears most plausible. The statue exemplifies the transmission and adaptation of classical models in provincial Roman art, reflecting Apsorus’s cultural engagement with modern metropolitan artistic trends.
Keywords: Apsorus; Augustan era; avgustejska doba; Caryatid; Dalmacija; Dalmatia; Grimani collection; kariatida; Osor; zbirka Grimani